2015
DOI: 10.7547/13-141.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity Level on the Longitudinal Arch in 7- to 12-Year-Old Rural and Urban Children

Abstract: These results suggest that the type of foot arch is influenced by parameters such as age, sex, and obesity level. High-arched foot seemed to be the most frequent pathologic abnormality in the examined group, and flatfoot, which was predominant in boys and obese children, diminished with age. High-arched foot was a more common MLA type than flatfoot regardless of obesity level assessed on the basis of body mass index and sum of three skinfolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…Woźniacka et al 35 , having examined 925 children, reported that the most commonly encountered deformity was a high-arched foot, i.e. in 523 children (56.5%) in the left foot, and in 592 children (64%) in the right foot.…”
Section: Discussionmentioning
confidence: 99%
“…Woźniacka et al 35 , having examined 925 children, reported that the most commonly encountered deformity was a high-arched foot, i.e. in 523 children (56.5%) in the left foot, and in 592 children (64%) in the right foot.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common are foot posture abnormalities - flat (pronating) foot and the hollow (supinating) foot 2–4 . As reported by some authors 3,5,6 , nowadays, high-arched feet are more often observed among children and adolescents than previously. This problem has been described by many authors 710 but the effects of different foot posture on pelvis and spine ailments are still little known.…”
Section: Introductionmentioning
confidence: 58%
“…The gender-based difference reported have contradictory evidence in the literature. Previous literature presents a predilection of flatfoot in males (Echarri and Forriol, 2003;Atamturk, 2009;Pauk et al, 2012;Woźniacka et al, 2015;Tong and Kong, 2016;Aenumulapalli et al, 2017).…”
Section: Prevalence In Adolescents Based On Gendermentioning
confidence: 99%
“…While presenting the conundrum of the association between flatfoot and age, the literature also presented contradicting evidence regarding the association of flatfoot with BMI. The evidentiary support leans toward the positive correlation between flatfoot and BMI on many accounts (Pfeiffer et al, 2006;Chen et al, 2009;Chang et al, 2010Chang et al, , 2012Tenenbaum et al, 2013;Ezema et al, 2014;Pita-Fernández et al, 2015;Woźniacka et al, 2015;Pourghasem et al, 2016;Gonzalez-Martin et al, 2017). Nonetheless, a study from does not hold the ground for adolescents.…”
Section: Association Of Flatfoot and Bmi In Adolescentsmentioning
confidence: 99%